Therapeutic improvement of CFTR function and reversibility of bronchiectasis in cystic fibrosis - Wielpütz, Mark Oliver; Mall, Marcus A. (The European respiratory journal, 2024)
The study by Cazier and co-workers promotes current efforts to diagnose and treat CF lung disease as early as possible in order to prevent structural lung damage, and to target initially reversible changes before persistent airway damage is established
Gesehen am 18.10.2024